Oferta dydaktyczna uniwersytetu. Potencjał i ograniczenia dla kształtowania kapitału społecznego w szkole wyższej - Wawrzyniak-Beszterda, Renata (Wydawnictwo Naukowe UAM, 2012)
The article presents issues related to the quality of the didactic offer of a university and the opportunities it creates for developing social capital at high school. The author’s argument is related to the results of the research conducted among the students of Adam Mickiewicz University in Poznan.
The didactic offer of a university. The potential and limitations on creating social capital at high school
Keywords: didactic offer of a university; social capital; high school